ANALISIS YURIDIS TERHADAP GUGATAN WANSPRESTASI TERKAIT DENGAN KOMPETENSI RELATIF (Perkara No.301/Pdt/G/2018/PN.kt.Pst) - Suhono (2023)
The implementation of agreements in buying and selling generally does not always run smoothly, because there are still problems in an agreement, especially regarding the rights and obligations of each party that has an interest in each other which cannot be fulfilled in accordance with the agreement that has been agreed upon. Problems caused by either party being negligent or intentional by not fulfilling the contents of the agreement or the existence of a coercive situation and cannot be controlled by every human being. This problem can lead to an action commonly referred to as default on an agreement that has become a mutual agreement by both parties. The causal factor with Defendant II not sending the return of sugar that had been taken from Defendant I's warehouse to be given back to the Plaintiff, was due to the Plaintiff's lack of caution in purchasing sugar through several intermediaries which resulted in losses suffered by the Plaintiff and Defendant I and also did not implement it. payment of value added tax (VAT) on the sale of sugar by Defendant II. As a result of these problems a lawsuit for default arose, while the relative competency exception filed by Defendant I was not considered by the Panel of Judges on the Principle of Objectivity with the legal standing of the parties. purchase of crystal sugar under the PTPN X brand that has been agreed upon by both parties.